PUBLIC AWARENESS ON EXISTING ENVIRONMENTAL HEALTH REGULATIONS AND ITS APPLICATION IN URBAN AND PERI-URBAN AREAS ADDIS ABABA ETHIOPIA - Desalegn, Tariku Berhanu; Dolamo, B L (Africa Journal of Nursing and Midwifery, 2016)
Background: Limited public awareness on existing environmental health regulations, failure to implement them and support their execution when violated often results in poor environmental situation. The purpose of this study was to assess the public knowledge of existing environmental health regulations and their applications in the urban and peri-urban environment of Addis Ababa. Â Setting: Urban and peri-urban areas of Addis Ababa, capital of Ethiopia. Â Methods: A descriptive study was conducted to assess the knowledge and practices of the study population regarding existing environmental health regulation: inbuilt environment, solid and liquid waste management, air and noise pollutions and their implementation.Â Six woredas from two sub cities of the Addis Ababa City Administration were purposely selected, and data collected from 845 (98.9% response rate) households. Â Results:Â Of selected regulations 56 % of participants knew the standards on environmental protection and sanitation and 40% reported knows regulations on solid waste management. Ownership of assets and education were strong determinants of public awareness of selected environmental health regulations. Â Conclusions:Â The public awareness on existing environmental health regulations in the study area was found to be low.